PENERAPAN APLIKASI PENDAFTARAN PEMANDU WISATA BERBASIS ANDROID - Kristina Kristina; Thommy Willay; Fransiska Sandova (INTEKSIS, 2022)
Tour guide is a profession in the field of tourism. Tour guides are responsible for accompanying tourists and providing directions and guidance to tourists. The tour guide must be able to explain the ins and outs of the places visited during the tour. Tour guides contain things that can guide visitors in exploring the entire area of tourist attractions and providing information about rides. Tourist guides are considered important because they are the reference for visitors in traveling at tourist sites. Tourism is everything related to tourism, including entrepreneurs of tourist objects and attractions and related businesses in that field. While traveling is a travel activity or part of these activities which is carried out voluntarily and temporarily to enjoy tourist objects and attractions. West Kalimantan is one of the tourist areas that has a variety of interesting tours. Most tourists visit West Kalimantan to see the natural and preserved culture and tourist attractions. Therefore, an Android-based application is designed to introduce these various tourist attractions to users, so new and appropriate innovations are needed to be better understood. So that users know some tourist attractions in West Kalimantan. This is the background for designing an application with the title "Designing an Android-Based Tourist Guide Application in West Kalimantan". The result of the research is to create an Android-based tourist guide application in West Kalimantan, which is expected to be able to provide convenience for users to find out tour guides and tourist information for West Kalimantan. The conclusion obtained by the author is that this application can display logins, registers, location of tourist attractions, show tour guides, verified status of tour guides and display detailed tour guide information.  Keywords: Apps, tour guides, Android, smartphones